OPTIMIZING MULTI-WALL PANEL CONFIGURATION FOR PANELIZED CONSTRUCTION USING BIM - Liu, Hexu; Holmwood, Benjamin; Sydora, Christoph; Singh, Gurjeet; Al-Hussein, Mohamed (Proceedings of International Structural Engineering and Construction, 2017)
With the rise of Building Information Modeling (BIM), off-site construction is gaining momentum in the construction industry. This construction method can benefit the industry through improved productivity and reduced waste. However, it also poses new challenges to building designers and construction practitioners with respect to building design and construction planning. For example, when designing building products and BIM models, designers needs to consider manufacturing process constraints in order to harness the benefits of manufacturing technology. This is in part due to the fact that, in the offsite construction paradigm, building design must be transformed from product-focused to manufacturing process-driven. At present, considerable human involvement and off-site construction knowledge are required to adapt building design (e.g., panelize building objects) for manufacturing processes within BIM environments. In this regard, this research contributes a BIM-based algorithm for panelizing building components. The proposed algorithm is capable of determining the granularity of wall panels and optimizing the configuration of multi-wall panels under engineering constraints, thereby improving productivity. The proposed approach is implemented within an Autodesk Revit environment through application programming interface. A case study of a residential building is used to demonstrate the proposed approach.